(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The role of women writers in Uzbek literature is incomparable. Speaking of prose and poetry, it is permissible to recognize the incomparable language and variety of themes of famous writers such as Zulfiya, Khalima Khudoyberdiyeva, Zebo Mirzo, Khosiyat Rustamova, Khalima Akhmedova, the authors of incomparable works. In the following article, in turn, we will provide more detailed information about one of the representatives of Uzbek modern literature, Khalima Khudoyberdiyeva, and her creative works